Combination of naproxen and a chemically‐stable eicosapentaenoic acid analog provide additive tumor protection in Pirc rats. Issue 12 (13th March 2023) - Beach, Ryan; Hatano, Yuichiro; Qiao, Yong; Grady, James; Sei, Shizuko; Mohammed, Altaf; Rosenberg, Daniel W.
Abstract: Colorectal cancer (CRC) is the second leading cause of cancer‐related deaths in the United States. Patients with the genetic disorder Familial Adenomatous Polyposis (FAP) develop hundreds to thousands of polyps that unless removed by prophylactic colectomy will progress to CRC at an early age. Nonsteroidal anti‐inflammatory drugs (NSAIDs) and the ω‐3 polyunsaturated fatty acid (PUFA) eicosapentaenoic acid (EPA), have been evaluated for their chemopreventive potential in delaying CRC onset in high‐risk patients. In our study, we determined whether the NSAID, naproxen, alone or in combination with a chemically‐stable EPA analog (TP‐252), affects tumor formation in the Apc Pirc rat model. When compared to control diet, animals fed naproxen or HD TP‐252 had 66% and 82% fewer tumors, respectively. However, animals fed a combination of naproxen and HD TP‐252, exhibited a 95% reduction in tumor formation and a 98% reduction in tumor volume, respectively. To elucidate potential mechanisms of tumor protection, a comprehensive, targeted lipidomic analysis was performed on colonic mucosa to determine changes in eicosanoid metabolism. Animals receiving TP‐252 alone or in combination with naproxen had significantly reduced mucosal levels of proinflammatory ω‐6 eicosanoids (PGE2, 5‐HETE and 14, 15‐DiHETrE), along with a simultaneous increase in anti‐inflammatory EPA‐derived ω‐3 eicosanoids. A comprehensive lipidomic analysis also uncovered several potential pharmacodynamic (PD) lipid biomarkers, including resolvin E2, 9‐HEPE, 12‐HEPE and 18‐HEPE, that were significantly correlated with tumor protection. Further studies with this drug combination should be focused on dose optimization and the role of EPA‐derived lipid mediators in CRC initiation and progression. Abstract : What's new? Patients with familial adenomatous polyposis develop hundreds of polyps that unless removed by prophylactic colectomy will progress to colorectal cancer at an early age. Here, the authors evaluated the chemopreventive efficacy of a novel, chemically‐stable eicosapentaenoic acid analog (TP‐252) in combination with the nonsteroidal anti‐inflammatory drug, naproxen in a colon cancer rat model with highly‐penetrant mutations. Tumor development was markedly impaired by the drug combination while eicosanoid metabolism showed a drastic shift toward potent anti‐inflammatory products. The findings point to several potential pharmacodynamic biomarkers for further clinical testing, including RvE2, 9‐HEPE, 12‐HEPE and 18‐HEPE.